SCAFFOLDING INTERACTION CYCLE IN READING TO LEARN PROGRAM - Silvia Widianingsih (Jurnal Semantik, 2012)
This study aims to investigate three steps (Prepare, Task and Elaborate) of scaffolding interaction cycle (Rose, 2008) in Reading to Learn program (Rose & Acevedo, 2006; Rose, 2008) with one teacher and fifteen students as the participants at a vocational high school. This study used a case study research design which employed two data collection techniques, i.e. observation and document analysis of students’ writing in Independent Writing stage. The study reveals three findings related to the research questions. First, the teacher used scaffolding interaction cycle almost in all stages in Reading to Learn program except for Preparing for Writing stage due to teacher’s misunderstanding toward the strategies used in this stage. Second, Prepare moves were mostly employed by the teacher in scaffolding interaction cycle because the students were still reluctant to actively engage in this program. Finally, the problems that the teacher found in the use of scaffolding interaction cycle in Reading to Learn program were related to teacher’s understanding, students’ questions, students’ passivity and big class. It is thus recommended to the teachers to more carefully plan the use of scaffolding interaction cycle in Reading to Learn program. Besides that, further research is expected to deal with more texts, more intensive support, bigger number of participants and longer time in conducting the program.